623=18z

Rewrite the equation as 18z=623.

18z=623

Multiply the numerator by the reciprocal of the denominator.

18z=6(32)

Cancel the common factor of 2.

Factor 2 out of 6.

18z=2(3)32

Cancel the common factor.

18z=2⋅332

Rewrite the expression.

18z=3⋅3

18z=3⋅3

Multiply 3 by 3.

18z=9

18z=9

Multiply each term by z and simplify.

Multiply each term in 18z=9 by z.

18z⋅z=9⋅z

Cancel the common factor of z.

Cancel the common factor.

18z⋅z=9⋅z

Rewrite the expression.

18=9⋅z

18=9z

18=9z

Rewrite the equation as 9z=18.

9z=18

Divide each term by 9 and simplify.

Divide each term in 9z=18 by 9.

9z9=189

Cancel the common factor of 9.

Cancel the common factor.

9z9=189

Divide z by 1.

z=189

z=189

Divide 18 by 9.

z=2

z=2

z=2

Solve for z 6/(2/3)=18/z